How to Make over 20% Efficient Perovskite Solar Cells in Regular (n–i–p) and Inverted (p–i–n) Architectures - Saliba, Michael; Correa-Baena, Juan-Pablo; Wolff, Christian M; Stolterfoht, Martin; Phung, Nga; Albrecht, Steve; Neher, Dieter; Abate, Antonio (Chemistry of materials, 2018)
Perovskite solar cells (PSCs) are currently one of the most promising photovoltaic technologies for highly efficient and cost-effective solar energy production. In only a few years, an unprecedented progression of preparation procedures and material compositions delivered lab-scale devices that have now reached record power conversion efficiencies (PCEs) higher than 20%, competing with most established solar cell materials such as silicon, CIGS, and CdTe. However, despite a large number of researchers currently involved in this topic, only a few groups in the world can reproduce >20% efficiencies on a regular n–i–p architecture. In this work, we present detailed protocols for preparing PSCs in regular (n–i–p) and inverted (p–i–n) architectures with ≥20% PCE. We aim to provide a comprehensive, reproducible description of our device fabrication protocols. We encourage the practice of reporting detailed and transparent protocols that can be more easily reproduced by other laboratories. A better reporting standard may, in turn, accelerate the development of perovskite solar cells and related research fields.